Probiotics and live biotherapeutic products aiming at cancer mitigation and patient recover - Schemczssen-Graeff, Zelinda; Pileggi, Marcos (Frontiers in Genetics, 2022)
Molecular biology techniques allowed access to non-culturable microorganisms, while studies using analytical chemistry, as Liquid Chromatography and Tandem Mass Spectrometry, showed the existence of a complex communication system among bacteria, signaled by quorum sensing molecules. These approaches also allowed the understanding of dysbiosis, in which imbalances in the microbiome diversity, caused by antibiotics, environmental toxins and processed foods, lead to the constitution of different diseases, as cancer. Colorectal cancer, for example, can originate by a dysbiosis configuration, which leads to biofilm formation, production of toxic metabolites, DNA damage in intestinal epithelial cells through the secretion of genotoxins, and epigenetic regulation of oncogenes. However, probiotic strains can also act in epigenetic processes, and so be use for recovering important intestinal functions and controlling dysbiosis and cancer mitigation through the metabolism of drugs used in chemotherapy, controlling the proliferation of cancer cells, improving the immune response of the host, regulation of cell differentiation and apoptosis, among others. There are still gaps in studies on the effectiveness of the use of probiotics, therefore omics and analytical chemistry are important approaches to understand the role of bacterial communication, formation of biofilms, and the effects of probiotics and microbiome on chemotherapy. The use of probiotics, prebiotics, synbiotics, and metabiotics should be considered as a complement to other more invasive and hazard therapies, such chemotherapy, surgery, and radiotherapy. The study of potential bacteria for cancer treatment, as the next-generation probiotics and Live Biotherapeutic Products, can have a controlling action in epigenetic processes, enabling the use of these bacteria for the mitigation of specific diseases through changes in the regulation of genes of microbiome and host. Thus, it is possible that a path of medicine in the times to come will be more patient-specific treatments, depending on the environmental, genetic, epigenetic and microbiome characteristics of the host.